A Study of the Influence of Marine Ranching Construction on Ecotourism: Take Wuzhizhou Island tourist area, Sanya for example - Chunhong LI; Yangle CHEN (Haiyang Kaifa yu guanli, 2022)
The construction of marine ranching could restore the marine ecological environment, recover marine fishery resources, and promote the sustainable development of marine fisheries. The construction of marine ranching in China began in the 1970s and has made great achievements. Many domestic scholars had also made plenty of achievements in the researches of marine ranching. Sanya Wuzhizhou Island marine ranching is a tropical island leisure tourism type marine ranching. Through the study of marine ranching in Wuzhizhou Island, it was found that the construction of marine ranching had brought significant ecological, economical, and social benefits to the tourist area. Besides, it had played a great role in the development of ecotourism as well.